2022
DOI: 10.1093/jaoacint/qsac130
|View full text |Cite
|
Sign up to set email alerts
|

3M™ Petrifilm™ Rapid Yeast and Mold Count Plate for the Enumeration of Yeasts and Molds in Dried Cannabis Flower: AOACOfficial MethodSM 2014.05

Abstract: Background The 3M™ Petrifilm™ Rapid Yeast and Mold (RYM) Count Plate is a sample-ready culture medium system which contains nutrients supplemented with antibiotics, a cold-water-soluble gelling agent, and an indicator system that facilitates yeast and mold enumeration. Objective The 3M Petrifilm RYM Plate was validated for the enumeration of yeast and mold in dried cannabis flower through the AOAC Emergency Response Validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Repay (2021) observed consistent and high recovery of TYM on Petrifilm™ medium. Schumacher et al (2022) observed greater morphological diversity of colonies when dishes were incubated at 25°C compared to 28°C, confirming that temperatures of 22–25°C are more suited for TYM growth.…”
Section: Discussionmentioning
confidence: 53%
“…Repay (2021) observed consistent and high recovery of TYM on Petrifilm™ medium. Schumacher et al (2022) observed greater morphological diversity of colonies when dishes were incubated at 25°C compared to 28°C, confirming that temperatures of 22–25°C are more suited for TYM growth.…”
Section: Discussionmentioning
confidence: 53%